2021
DOI: 10.1002/jemt.23799
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic techniques to evaluate the biofilm formation ability of a marine bacterium Pseudomonas aeruginosa PFL‐P1 on different substrata

Abstract: Biofilm formation in bacteria is strongly affected by the nature of substrata. Different substrata such as glass, polystyrene, steel, ceramic, and rubber were used to assess the biofilm forming ability of a marine bacterium Pseudomonas aeruginosa PFL‐P1 using a scanning electron microscope (SEM), atomic force microscope (AFM), and confocal laser scanning microscope (CLSM). The bacterium formed dense biofilms with varied aggregation on different substrata. SEM study revealed small rod‐shaped cells with diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The characterization of microbial topographies is a growing field ( 31 38 ) but with limited focus on the temporal dynamics of the colony. The experimental difficulty in measuring biofilm heights with sufficient precision over many different time scales in a nondestructive manner has limited our understanding of this fundamental phenomenon ( 39 ).…”
mentioning
confidence: 99%
“…The characterization of microbial topographies is a growing field ( 31 38 ) but with limited focus on the temporal dynamics of the colony. The experimental difficulty in measuring biofilm heights with sufficient precision over many different time scales in a nondestructive manner has limited our understanding of this fundamental phenomenon ( 39 ).…”
mentioning
confidence: 99%
“…Biofilm is the major mode of bacteria life in the environment, including the marine habitats, enabling the formation of complex microbial communities [ 74 , 75 ]. Several studies have reported that marine strains of P. aeruginosa are capable of forming biofilm [ 76 , 77 ]. Furthermore, our results indicate that the marine and clinical isolates of P. aeruginosa tested express factors related to the virulence of this bacterium (secretion of ExoS and ExoU toxins through the T3SS, as well as production of pyocyanin, elastase, and rhamnolipids).…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of microbial topographies is a growing field( Dervaux et al, 2014 ; Larimer et al, 2016; Kesel et al, 2017 ; Werb et al, 2017 ; Schiebel et al, 2020 ; Paula et al, 2020 ; Hayta et al, 2021; Mahto and Das, 2021 ), but with limited focus on the temporal dynamics of the colony. The lack of clarity about vertical growth dynamics is due in part to the experimental difficulty in measuring the height of a biofilm with sufficient precision over many different time scales in a non-destructive manner( Huang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of microbial topographies is a growing field(3138), but with limited focus on the temporal dynamics of the colony. The lack of clarity about vertical growth dynamics is due in part to the experimental difficulty in measuring the height of a biofilm with sufficient precision over many different time scales in a non-destructive manner(39).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation